I have a bad feeling about this - Strand, Jeff (Sourcebooks Fire, 2014)
Everything unathletic sixteen-year-old Henry was dreading about survival camp turns out to be true--or even worse--when armed killers arrive and survival takes on a whole new meaning for the campers.